2021
DOI: 10.1155/2021/5021868
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Microemulsion Flooding Study to Increase Low Viscosity Oil Recovery Using Glass Micromodel

Abstract: The growing demand for clean energy can be met by improving the recovery of current resources. One of the effective methods in recovering the unswept reserves is chemical flooding. Microemulsion flooding is an alternative for surfactant flooding in a chemical-enhanced oil recovery method and can entirely sweep the remaining oil in porous media. The efficiency of microemulsion flooding is guaranteed through phase behavior analysis and customization regarding the actual field conditions. Reviewing the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Energies 2022, 15, 4906 18 of 20 Glass micromodel experiments, on the other hand, will allow for continuous real-time visualization of fluid flow processes throughout the experiment [45][46][47], but an investigation under reservoir conditions will require glass that can withstand high temperatures. Because glass may not be able to resist excessive pressure, a confining cell for the glass may be required for safety purposes [48] but adapted with ultrasound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energies 2022, 15, 4906 18 of 20 Glass micromodel experiments, on the other hand, will allow for continuous real-time visualization of fluid flow processes throughout the experiment [45][46][47], but an investigation under reservoir conditions will require glass that can withstand high temperatures. Because glass may not be able to resist excessive pressure, a confining cell for the glass may be required for safety purposes [48] but adapted with ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…The confining pressure, core sizes, and type of fluid to be injected will all influence the design and material to be used. Glass micromodel experiments, on the other hand, will allow for continuous realtime visualization of fluid flow processes throughout the experiment [45][46][47], but an investigation under reservoir conditions will require glass that can withstand high temperatures. Because glass may not be able to resist excessive pressure, a confining cell for the Oil viscosity was reduced by ultrasonic, and the reduction was higher when the power and frequency were increased.…”
Section: Observationsmentioning
confidence: 99%
“…It was also concluded that the designed flow model allowed the visual evaluation of the sweep efficiency by allowing more complex reservoir flow experiments to be carried out. Hematpur et al 172 used a low-pressure micromodel apparatus to evaluate surfactant-based microemulsions. Two patterns were designed with different coordination numbers and pore-throat ratios (Figures 18a and b).…”
Section: Surfactant-based Oil Recovery Studiesmentioning
confidence: 99%
“…Flow patterns designed by Hematpur et al Reproduced with permission from ref . Copyright 2021 Hindawi.…”
Section: Surfactant-based Oil Recovery Studiesmentioning
confidence: 99%
“…Recently, microemulsions have been used in EOR processes in which chemicals are used for oil recovery. They also give low IFT and subsequently mobilize the trapped crude oil after secondary recovery, for this reason, they are found quite appropriate for EOR processes. , Due to different conditions such as type and amount of surfactant and cosurfactant, salinity, temperature, etc., microemulsions can have different phase behaviors, and each of these phases is called Winsor. , According to the results of previous researchers, usually three types of Winsors containing Winsors I (oil in water), II (water in oil), and III (bicontinuous oil and water or middle phase microemulsion) are formed in oil reservoirs in EOR processes.…”
Section: Introductionmentioning
confidence: 99%